Synthesis and crystal structure (E)-1-(4-bromo-2-hydroxyphenyl)-3-(dimethylamino)prop-2-en-1-one, C11H12BrNO2 - Dong Zhang-Chao; Zheng Liang-Liang; Pan Bo-Wen; Shi Yang; Zhou Ying (Zeitschrift für Kristallographie - New Crystal Structures)
C11H12BrNO2, monoclinic, P21/n (no. 14), a = 7.5143(12) Å, b = 11.8968(15) Å, c = 12.9852(13) Å, β = 105.575(14)°, V = 1118.2(3) Å3, Z = 4, R gt(F) = 0.0607, wR ref(F 2) = 0.1615, T = 293.00(10) K.